EVALUATION OF THE PHLORIDZINE AND ICARIIN INFLUENCE RATE ON THE LAVEL OF WORKINC CAPACITY AND NEUROLOGICAL STATUS OF THE ANIMALS IN THE CONDITIONS OF EXHAUSTING PHYSICAL AND PSYCOEMOTIONAL STRESSES - A. V. Voronkov; I. N. Dyakova; D. I. Pozdnyakov; N. A. Muravyova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
We have conducted a study about the influence of natural flavonoids of phloridzine and icariins on the working capacity and a state of neurological status of animals in conditions of long exhausting physical and psychoemotional stresses. We have used outbred male mice weighing 20-25 g in the experiment. The compounds under study were administered per os at dose of 100 mg/kg 60 minutes before the stresses modeling. Physical and psychoemotional stresses were modeled on a forced swimming test with 20% stress from an animal weight during 10 days. After that psychoemotional state of animals was evaluated in tests of "open field" and "elevated plus maze". As the result of the experiment, we have established that phloridzine application conduced the increase of working capacity of animals, while activity peak fell on the 7th day of administration with stable indices, which characterized psychoemotional state of animals. The administration of icariin led to the working capacity reduction of mice by 44.6%  against the original indices of this group and by 55% in comparison with control animals, decrease of motion and orient-exploratory activity in the tests of "open field" and "elevated plus maze".